In Vitro Evaluation of Bacterial Bioagents and Fungicides Efficiency Against Rhizoctonia Solani Isolates the Causal agent of Black Scurf Disease of Potato - Ghazala, Alsadek M. (Scientific Journal for Faculty of Science-Sirte University, 2021)
The efficacy of two isolates of bacterial bioagents and two fungicides via, Rhizoctonia solani isolates were evaluated in vitro. In the dual culture assays, significance inhibition ratio of R. solani hyphal growth was obtained in all treatments of Pesudomonas fluoresnces and Bacillis subtilis compared to control. Also, Bacillus subtilis exhibit the highest significant suppression for the mycelial growth of R. solani isolates more than Pseudemonas fluorescens, and the ratios of inhibition differed according to the bioagents and R. solani isolates similar to those results in antifungal activity technique. The volatile metabolite studies revealed that in the first period (three days) inhibition percentage significantly differed according to the tested isolates of R. solani and the applied bioagents, B. subtilis gave the highest inhibition (57.41%) in R. solani isolate 3. Similarly in P. fluoresnces treatments, the highest inhibition was (57.41%) was detected in isolate 3 of R. solani considering that the second tested time period (five day inoculation). B. subtilis showed highest inhibition value on isolate 1, on the other hand P. flouresnce showed high value of inhibition on isolate 2, whereas the lowest inhibition values were produced on isolate 1.Non volatile activity both bacterial bioagents isolates showed different values of inhibition on R. solani isolates. On the other hand, Rezolex was most effective against R. solani at two concentrations (0.2 and 0.3), however Topsin-M showed fluctuate inhibition values at two concentration used (0.04% and 0.075%). Further incubation of plates showed suppressed the formation of sclerotia by all the antagonists tested. The results implied that the extent of inhibition by B. subtilis and P. fluoresnces rovides the use of excellent potential antagonists capable of controlling the R. solani in vitro.